Participatory Approaches in Agricultural Research: A Case Study of the Andhra Pradesh Netherlands Biotechnology Programme - G. Pakki Reddy,; P.S. Janaki Krishna, (Journal of Agricultural Extension Management, 2025)
In the continuum of basic to applied to adaptive research in agriculture, farmers were seen as valuable source of knowledge, which in the process was respected and empowered. However, the mainstream research and development (R&D) organizations still have to acknowledge farmers as partners of technology development. In addition to the on-farm research and extension activities, an exclusive domain of development intervention is needed to enhance the farmers' capacities in developing new technologies. In this endeavour, a number of tools and techniques were developed by the concerted efforts of sociologists, economists and scientists. Among these, the most widely used tools are the rapid rural appraisal ((RRA), participatory rural appraisal (PRA), participatory technology development (PTD) and interactive bottom up (/BU) approaches. The APNL Biotechnology Programme is one such programme which uses IBU approach for developing agricultural biotechnologies for small-scale farmers and tries to assess its impact. Programme involves various stakeholders including farmers, scientists, extensionists, NGO staff, policy makers, etc. In the technology development process